Indian Timbers for Veneering - A Review - Prakash, V.; Singh, M. P.; Uday, D. N.; Sujatha, D.; Kiran, M. C.; Murthy, Narasimha (Indian Forester, 2021)
Conservation oriented forest management policies and total ban on commercial logging from natural forest has led the plywood industry in India to a situation of shortage of traditional timber raw material which is used for manufacturing wood based panels. The shortage of raw materials has forced many wood based product mills to operate below their installed production capacities. The wood based industries in India are managing to survive on the availability of timber outside forest, secondary species and other lesser known Indian hardwoods. The industry is dependent on imported timber species to some extent as a source of raw material. Under this circumstance, the study on lesser known Indian hardwoods which can be grown in agro forestry and farm forestry plantation will help in making use of these species for plywood manufacturing and thereby ensuring uninterrupted supply of raw materials for production of plywood and other wood based panels. Keeping this in view, a series of studies has been carried out at Indian Plywood Industries Research and Training Institute (IPIRTI) to investigate the suitability of secondary species of timbers or lesser known Indian hardwoods especially the short rotation plantation grown timbers for the manufacture of plywood. This is a compilation of the outcome of such studies carried out at IPIRTI.